Disease: Social business for a malaria free world -BASF Grameen Limited - Munni, Sheikh Rubaiya Sultana; Nahiduzzaman, Kh Md (© 2014 Springer-Verlag Berlin Heidelberg, 2016)
This article was published in Social Business: Theory, Practice, and Critical Perspectives [© 2014 Springer-Verlag Berlin Heidelberg] and the definite version is available at: http://link.springer.com/chapter/10.1007%2F978-3-642-45275-8_5